2016
DOI: 10.1590/1519-6984.07615
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization of pollens from three Apiaceae species and their ingestion by twelve-spotted lady beetle (Coleoptera: Coccinellidae)

Abstract: Larvae and adults of certain species of predator lady beetles feed on pollen, guaranteeing their survival, and at times, reproduction in the absence of preferred prey. Palynology, therefore, may contribute in the investigation of botanical families visited by these predators in order to obtain this floral resource. There are records of the visitation of Apiaceae flowers by Coleomegilla maculata DeGeer, 1775 (Coleoptera, Coccinellidae), but not the ingestion of their pollen grains by this lady beetle. The exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…A detailed study of the fennel pollens (Foeniculum vulgare) was recently published (D'Avila et al, 2016). In the present study, examination of more than fifty pollen grains (seen in equatorial or longitudinal views) confirms this diagnosis.…”
Section: Pollen Grainssupporting
confidence: 80%
“…A detailed study of the fennel pollens (Foeniculum vulgare) was recently published (D'Avila et al, 2016). In the present study, examination of more than fifty pollen grains (seen in equatorial or longitudinal views) confirms this diagnosis.…”
Section: Pollen Grainssupporting
confidence: 80%
“…Scanning electron microscopy analysis of bee pollen samples, presented in Figure 1 and Table 2, showed that the botanical origin of each bee pollen sample according to its predominant pollen grains was as follows: the botanical origin of bee pollen sample from LARACHE was Coriandrum sativum (Apiaceae) (70%), the botanical origin of bee pollen sample from KHENICHAT was Ulex europaeus (Fabaceae) (73%), the botanical origin of bee pollen sample from HED KOURT was Scorzonera cana (Asteraceae) (77%), the botanical origin of bee pollen sample from KENITRA was Trifolium pretense (Fabaceae) (76%), the botanical origin of bee pollen sample from FEZ was Ulex europaeus (Fabaceae) (64%), the botanical origin of bee pollen sample from SEFROU was Reseda luteola (Resedaceae) (60%), the botanical origin of bee pollen sample from ARFOUD was Spiraea salicifolia (Rosaceae) (68%), and the botanical origin of bee pollen sample from TAZA was Lamium galeobdolon (Lamiaceae) (59%). e bee pollen identification was carried out by comparing the morphology, sizes, and exine ornamentations of bee pollen studied to that described elsewhere [20][21][22][23][24][25][26]. Louveaux et al reported that when the percentage of pollen grains is >45% of total, the sample is classified as monofloral [9].…”
Section: Botanical Identification Of Bee Pollen By Scanning Electronmentioning
confidence: 99%
“…Higher fecundity was also reported for H. convergens (729.15 eggs per female) reared on Aphis craccivora Koch, 1854 (Hemiptera: Aphididae) (El-Heneidy et al, 2008). The causes of variation in the fecundity of coccinellids are diverse and depend on several factors such as temperature, photoperiod, age of the parents, length of the oviposition period, and quality and quantity of food (Nedvěd and Honěk, 2012;D'Ávila et al, 2016;Lima et al, 2018).…”
Section: Discussionmentioning
confidence: 99%